Cell Contact-Dependent Increase in Membrane D-Galactopyranosyl-Like Residues on Normal, But Not Virus- or Spontaneously-Transformed, Murine Fibroblasts - Nicolson, Garth L. (1973)
Ricinus communis agglutinin (a lectin specific for β-D-galactopyranosyl-like oligosaccharide residues) was used to investigate differences in lectin-binding sites on normal 3T3 and transformed SV3T3 and 3T12 cells grown to various cell densities in culture. The agglutinability of SV3T3 cells by R. communis agglutinin decreased when cells were grown to confluency or to a point where the cells were in contact. The agglutinability of 3T3 cells also decreased at confluency, but this result was variable and not as dramatic as with SV3T3 cells. Saturation-binding experiments performed at 4° with (125)I-labeled R. communis agglutinin were used to monitor the number of lectin-binding sites on cells grown to different densities. Transformed cells (SV3T3 and 3T12) did not show cell-culture density-dependent changes in R. communis sites; sparse, touching, and confluent transformed cells had equivalent numbers of sites. However, touching (or confluent) 3T3 cells possessed 2.5-times the number of R. communis sites per cell compared to growing, sparsely populated 3T3 cells. When growing sparse 3T3 cells are compared to growing SV3T3 or 3T12 cells, there are 5-times R. communis sites per unit surface area on the transformed cells. The change in R. communis sites during cell growth in culture is discussed in relation to membrane fluidity and topography of plasma membrane oligosaccharides and glycosyl transferases, which can modify cell surfaces at contact.